First report of the genus Spinomarmessoidea (Phasmatodea, Lonchodidae, Necrosciinae) from China, with the description of a new species - Gao, Hao-Ran; Yong-He Li, (Zootaxa, 2023)
The recently described genus Spinomarmessoidea is comprised of only 2 species from Peninsular Malaysia. The 3rd species of this genus, Spinomarmessoidea damingensis sp. nov. is described from Guangxi Province, China. The new species represents the first record of this genus in China. The granulose head of new species without large spines and mesonotum with short spines are distinguished from the other 2 species. A key to the female of this genus is compiled. Type materials are deposited in the Yunnan Agricultural University (YNAU).